An unusual case of polymicrobial anaerobic bacteraemia in a male with ureteral calculi. Issue 3 (September 2014) - Chakhtoura, Nadim G. El; Khatri, Asma; Jacobs, Michael R.; Wnek, Maria D.; Jump, Robin L. P.
Abstract : Introduction: We describe an unusual case of anaerobic bacteraemia caused by Fusobacterium gonidiaformans and Peptoniphilus asacchacrolyticus, both commensal organisms normally found within human oropharyngeal, gastrointestinal and genitourinary tracts. Case presentation: One week following a routine colonoscopy with polypectomy, a 65‐year‐old male with renal calculi was admitted with a 3‐day history of severe abdominal pain and chills. He required urgent placement of a percutaneous nephrostomy tube. Urine cultures were negative but blood cultures were positive for Fusobacterium gonidiaformans and Peptoniphilus assachacrolyticus . Conclusions: We hypothesized that, following his colonoscopy, the patient developed transient bacteraemia with commensal gut organisms. In the setting of multiple ureteral calculi, this transient bacteraemia became a clinically significant infection, manifesting as acute ureterolithiasis with concurrent bloodstream infection. The routine collection of blood for anaerobic culture led to pathogen identification and appropriate antimicrobial therapy.